Advertising and Brand speech directed at Generation Z: Ethnographic study of a digital community - Rodrigo Martín, Luis; Mañas Viniegra, Luis; Núñez Gómez, Patricia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The object of the research is to know the main characteristics of generation Z as a target audience for advertising campaigns. To this end, a virtual community has been created that explores the levels of acceptance and rejection of different advertising issues, from content creation to the representation of Generation Z itself. The methodology used is qualitative and consisted of participant observation within the framework of digital ethnography. The results obtained allow us to draw an accurate description of the concerns of a generation that establishes new ways of relating to technology and the creation of content.